Numerical Solutions of Transonic to Supersonic Flow over Backward-Forward Facing Step with Heat Flux Conditions - Jeatrakul, Karn; Prapamonthon, Prasert; Tanpradit, Ditthaphat; Wongsatanawarid, Atikorn; Hao, Zhanzhou; Sun, Zhenxu; Yin, Bo (My University, 2026)
Flows phenomena over a backward-facing step (BFS) and a forward-facing step (FFS) are critical for understanding flow physics in engine, aerodynamic, heat transfer systems. Given the rapid advancement of high-speed technology, the presence of shock waves and aerodynamic heat can have an impact on flow physics, thereby emphasizing the importance of high-speed flow over BFS and FFS with heat transfer. This paper presents numerical solutions of steady two-dimensional viscous turbulent flow over a continuous backward-forward facing step (BFFS) in the transonic to supersonic regime with heat flux conditions using STAR-CCM+. The compressible air and k-ϵ turbulence model are used for the simulations. The effects of inlet Mach numbers ranging from 0.8 to 3.0 and bottom step heat fluxes varying from 0.5 to 10.0 kW/m2 on flow physics are investigated. Numerical results depict flow phenomena such as flow separation, recirculation, and shock wave, as well as thermal distribution. Furthermore, the results show that variations in the inlet Mach number affect flow behaviors, while higher heat fluxes cause dramatical changes in Nusselt number, especially, in the BFS corner for transonic flow.
Keywords: Computational fluid dynamics (CFD); heat transfer; supersonic flow